SURFACE MODIFICATION METHODS FOR INCREASING THE SERVICE LIFE OF MECHANICAL ENGINEERING COMPONENTS - R.T. Nurullaev; B.I. Rakhimboev (International Journal of Literature and Language Studies, 2026)
Mechanical engineering components are often subjected to severe operating conditions such as friction, wear, corrosion, and high mechanical loads. These factors significantly reduce the service life and reliability of machine parts. Surface modification technologies have become an effective approach to improving the durability and performance of mechanical components. This study investigates various surface modification methods used to enhance the service life of mechanical engineering components. The research focuses on coating technologies, surface hardening methods, and advanced material treatment techniques. Analytical and comparative research methods were applied based on scientific literature and industrial practices. The results show that surface modification technologies significantly improve wear resistance, corrosion resistance, and mechanical strength of machine components. Furthermore, modern techniques such as laser surface treatment and plasma coating provide higher efficiency and reliability compared to traditional methods. The study highlights the importance of advanced surface engineering technologies in improving the performance and service life of mechanical engineering components.